HIV specific responses induced in nonhuman primates with ANRS HIV-Lipo-5 vaccine combined with rMVA-HIV prime or boost immunizations. Issue 20 (11th May 2015) - Dereuddre-Bosquet, Nathalie; Baron, Marie-Laurence; Contreras, Vanessa; Gosse, Leslie; Mangeot, Isabelle; Martinon, Frédéric; Yousfi, Rahima; Clayette, Pascal; Levy, Yves; Le Grand, Roger; Vaccine Research Institute
Highlights A priming/booster strategy combining HIV LAI lipopeptides and rMVA enhances specific T-cell responses. rMVA immunizations, unlike HIV-Lipo-5 immunizations, do not elicit detectable anti-HIV Ab response. Lipopeptide priming and live attenuated virus vector booster combination may be appropriate for therapeutic immunization in HIV infected patients.